La triangulación metodológica: sus principios, alcances y limitaciones (2000)
ABSTRACT: This article tries to gather the basic and relevant data on methodology triangulation and to approach primarily to the principles behind its use, potentiality, and scope, its developments and limitations, and some alternative proposals to overcome it. In this way, it is an attempt to become operative the concepts and to present the procedures to perform it rigorously. First the concepts and kinds of triangulation are presented. Second, the principles and difficulties are shown. The implicit behind this article is the complement among methods. We pretend that the nature of objects direct the selection of methods and the most-efficacious techniques to approach and notice the phenomena socially relevant to be studied.